In memoriam Céline - Maxim Görke (Recherches Germaniques)
Starting from the fact that Louis-Ferdinand Céline’s name is a recurrent reference in Rolf Dieter Brinkmann’s work, the article takes up this hitherto poorly explored intertextual clue and demonstrates, based on a cross-reading of In der Grube and Journey to the End of the Night, what the first text owes to the second. The focus is placed on the literary genres revisited by the two texts and, even more, on some of the motives that one borrows from the other. The results show that Céline’s influence on Brinkmann’s writing goes far beyond what was known until now.